Production of Ternary Blend Binder as an Alternative to Portland Cement. Issue 1 (March 2021) - Al-Mamoori, Shahad F.; Shubbar, Ali A.; Al-Khafaji, Zainab S.; Nasr, Mohammed Salah; Alkhayyat, Ahmed; Al-Rifaie, Ali; Al-Mufti, Rafal Latif; Sadique, Monower; Hashim, Khalid
Abstract: Environmental pollution and the relatively high cost of waste disposal have been a major focus for scientists around the world, leading researchers to find a solution to reuse waste materials in different applications. Additionally, landfills are considered one of the biggest crisis facing the Iraqi government. Therefore, this study aims to present a new ternary mixture that consists of OPC in addition to Pulverized Fuel Ash (PFA), Ground Granulated Blast Furnace Slag (GGBS) by utilizing it as a partial substitution of cement. A new ternary mortar mixtures containing four substitution levels of cement with GGBS and PFA (0%, 30 %, 50% and 70% by weight) were carried out. The Ultrasonic Pulse Velocity (UPV) and compressive strength tests were adopted to show the influence of GGBS and PFA on mechanical features of cement mortar. Findings indicated that, the compressive strength values were reduced with increasing the GGBS and PFA proportions at all curing ages. For 70% replacement, the compressive strength values were the lowest values comparison with that for control specimens. In contrast, the GGBS and PFA had a negative and positive impacts on the UPV of mortar depending on the substitution ratio. At 30 % substitution levels, the velocity value was enhanced, while other substitution ratios affected negatively on the UPV values.